2000
DOI: 10.1039/b008210o
|View full text |Cite
|
Sign up to set email alerts
|

A ten channel fibre-optic device for distributed sensing of underground hydrocarbon leakage

Abstract: With millions of fuel storage tanks and oil pipelines installed around the world, there is inevitably frequent leakage of potentially hazardous hydrocarbons. As many of these installations are below ground, it can often be many years before the extent of the leak is discovered. We have previously reported the development of a sensor for the detection of such subterranean leaks, using infrared reflectometry to interrogate a hydrocarbon sensitive membrane. However, a single sensor cannot provide any information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…There is no doubt that the use of fiber-optic technology has increased the versatility of optical sensors and this makes them a powerful analytical tool. A number of groups have studied the response characteristics of various polymer-coated fiber optic sensors for the detection of a wide range of hydrocarbons in waters and soils ( ). These studies have demonstrated that low hydrocarbon levels can be detected rapidly (<1 min) only under certain conditions.…”
Section: Transducersmentioning
confidence: 99%
“…There is no doubt that the use of fiber-optic technology has increased the versatility of optical sensors and this makes them a powerful analytical tool. A number of groups have studied the response characteristics of various polymer-coated fiber optic sensors for the detection of a wide range of hydrocarbons in waters and soils ( ). These studies have demonstrated that low hydrocarbon levels can be detected rapidly (<1 min) only under certain conditions.…”
Section: Transducersmentioning
confidence: 99%
“…The novel design of the sensor head ( Fig. 1) incorporates a highly reflective hydrocarbon-specific membrane [3], supplied by Pall-Gelman Ltd (Portsmouth, U.K.). The membrane is protected on the exterior face by a 1-mm aluminium mesh.…”
Section: Sensor Designmentioning
confidence: 99%
“…Initially designed for soil and sediment monitoring, the sensors have been shown to respond to phase hydrocarbon contamination [3,6]. Recognising the potential risk to European water resources, determining the response to a range of hydrocarbons in water may enable initial quantification for pollution incidents.…”
Section: Preliminary Experimental Procedures and Aimsmentioning
confidence: 99%